Health Surveillance Integration System web-based for Health Centers - Qashlim, Akhmad; Andi, Riswandi; Khairat, Ul (Journal of Intelligent Computing & Health Informatics, 2021)
Efforts to improve analytical skills provide recommendations and improve partner’s cooperation in order to strengthen the surveillance system in each Health Center unit that can be utilized by the field of epidemiology for managers / structural and functional. So we need an automated system that is able to process and integrate disease data into surveillance data. This automated system can be created using web-based information technology. This study aims to design a web-based information system that processes disease data taken from patient medical records and disease reports at three health centers, namely Massenga Health Center, Matakali Health Center, and Pekkabata Health Center then presented as disease surveillance data at the Health Office. The focus of surveillance is on the disease, not the individual. Qualitative methods in this study were used to analyze each system at each health center. This system is built using the PHP and MySQL programming languages using the concept of database integration. This system will collect data from three samples of Health Center, then the incoming data will automatically be processed and analyzed so as to produce objective, measurable information that can be compared over time between health center as decision making material. The results of this study are surveillance data regarding the information of diseases and trends in diseases such as DBD, TBC, ISPA, Hipertensi at certain timeframes in each Health.